Pasingtabi king Aldo ampong Angin (homage to the Sund and the Wind) traditions in Kapampangan vernacular architecture - Santos, Michaela Rosette M.; Bulaong, Carmen Bettina S. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
Vernacular architecture in the Philippines is manifested in the domestic structures that are made of materials readily available in the locality, and built based on the needs of users, as a natural response to geography and climate. Different local shelters in various regions of the country have been documented and classified according to geography and ethnology. Several types of these houses were recorded in the mountainous Cordillera region, with varying attributes described, depending on the culture and needs of each tribe that inhabit the region. A number of dwellings found in the coastal areas of Mindanao, that exhibit distinct features, have also been documented. However, in the plains and grasslands, only one type of house, the "bahay kubo" or the cube house has been identified. Not much is written on the divergent houses that can be found in the lowlands. This study delves in exploring the distinct domestic typologies in the province of Pampanga that have not been examined before. The unassuming character of the pre-colonial Kampampangan architecture, have adorned the exquisite culture of Pampanga, guided by the little known indigenous building tradition "Pasingtabi king Aldo ampong Angin" (Homage to the Sun and Wind). This folk construction belief, used by the traditional carpenters, has long been forgotten. The aim is to organize a body of knowledge that will strongly illustrate the unique identity of Kapampangan vernacular architecture and the existence of a localized building model that could enrich the resources of the contemporary built environment practices and be used as a manual in building design and construction giving respect to Mother Nature.
includes appendices
Thesis (Master of Architecture) -- University of the Philippines Diliman
Keywords: Vernacular architecture -- Pampanga; Architecture, Domestic -- Pampanga